Tumor Associated Macrophages: Origin, Recruitment, Phenotypic Diversity, and Targeting - Hourani, Tetiana; Holden, James A.; Li, Wenyi; Lenzo, Jason C.; Hadjigol, Sara; O’Brien-Simpson, Neil M. (Frontiers in Oncology, 2021)
The tumour microenvironment (TME) is known to have a strong influence on tumourigenesis, with various components being involved in tumour suppression and tumour growth. A protumourigenic TME is characterised by an increased infiltration of tumour associated macrophages (TAMs), where their presence is strongly associated with tumour progression, therapy resistance, and poor survival rates. This association between the increased TAMs and poor therapeutic outcomes is stemming an increasing interest in investigating TAMs as a potential therapeutic target in cancer treatment. Prominent mechanisms in targeting TAMs include: blocking recruitment, stimulating of re-polarization, and the depletion methods. For enhancing targeting specificity multiple nanomaterials are currently being explored for the precise delivery of chemotherapeutic cargo, including the conjugation with TAM-targeting peptides. In this paper, we provide a focused literature review on the biology of macrophages in relation to their role in tumourigenesis. First, we discuss the origin, recruitment mechanisms, and phenotypic diversity of TAMs based on recent investigations in the literature. Then the paper provides a detailed review on the current methods of targeting TAMs, including the use of nanomaterials as novel cancer therapeutics.